Exploring telecollaboration through the lens of university students: a Spanish-Cypriot telecollaborative exchange - Nicolaou, Anna; Sevilla-Pavón, Ana (My University, 2016)
This paper examines university students’ views about a Cypriot-Spanish telecollaboration project through which participants used Google+ Communities for intercultural exchange over the course of one semester. The project was established through the UNICollaboration platform and it involved first-year students at the Cyprus University of Technology (CUT) and the University of Valencia (UV). The telecollaboration tasks and activities were embedded in the students’ English for Specific Purposes modules. The project aimed at developing students’ cultural awareness and competence learning, as well as at enhancing their motivation to learn English at university level. This paper outlines the pedagogical goals of the project, the design of tasks, the communication modes, the digital tools used for interaction and task completion, and the targeted competences. Using qualitative data through focus groups interviews with the students who participated in the project, the paper aims at exploring telecollaboration from the student experience perspective, demonstrating the benefits and challenges of online intercultural exchanges.
Keywords: Telecollaboration; Design-based research; Students’ views